Detection of fixed and variable targets in the monkey prefrontal cortex. - Kusunoki, M; Sigala, N; Gaffan, D; Duncan, J (Oxford University Press, 2009)
Behavioral significance is commonly coded by prefrontal neurons. The significance of a stimulus can be fixed through experience; in complex behavior, however, significance commonly changes with short-term context. To compare these cases, we trained monkeys in 2 versions of visual target detection. In both tasks, animals monitored a series of pictures, making a go response (saccade) at the offset of a specified target picture. In one version, based on "consistent mapping" in human visual search, target and nontarget pictures were fixed throughout training. In the other, based on "varied mapping," a cue at trial onset defined a new target. Building up over the first 1 s following this cue, many cells coded short-term context (cue/target identity) for the current trial. Thereafter, the cell population showed similar coding of behavioral significance in the 2 tasks, with selective early response to targets, and later, sustained activity coding target or nontarget until response. This population similarity was seen despite quite different activity in the 2 tasks for many single cells. At the population level, the results suggest similar prefrontal coding of fixed and short-term behavioral significance.